Cost of human papillomavirus vaccine delivery in a single-age cohort, routine-based vaccination program in Senegal. (31st March 2022) - Brennan, Timothy; Hidle, Anna; Doshi, Reena H.; An, Qian; Loharikar, Anagha; Casey, Rebecca; Badiane, Ousseynou; Ndiaye, Alassane; Diallo, Aliou; Loko Roka, Jerlie; Mejia, Nelly; Abimbola, Taiwo
Abstract: Introduction: In 2018, Senegal introduced human papillomavirus (HPV) vaccine into its routine immunization program for all nine-year-old girls nationwide. We evaluated the costs of Senegal's introduction of HPV vaccine via this delivery approach. Methods: We conducted a retrospective, incremental, ingredients-based cost evaluation from the provider perspective. The study timeframe included Senegal's first planning meeting in 2018 through data collection in early 2020. We collected costs from all involved units at the national and regional levels. A multi-stage cluster sampling approach was used to obtain a nationally representative sample of districts and health facilities. Weights were applied to costs from sampled units to estimate costs across all units. The cost evaluation was based on four dimensions: program activity, resource input, payer, and administrative level. Total costs were divided by the number of HPV doses administered to determine cost per dose and per dimension. Results: Excluding vaccine program activity costs, the total financial and economic delivery costs of Senegal's HPV vaccination program were US$ 1, 152, 351 and US$ 2, 838, 466, respectively (US$ 3.07 and US$ 7.56 per dose, respectively). A total of 375, 608 HPV vaccine doses were administered during the cost evaluation. Training and per diem represented the largest shares of financial costs. Service delivery and personnel time accounted for the largest shares of economic costs. By administrative level, district and health facility levels had the largest shares of financial and economic costs, respectively. Senegal's Ministry of Health accounted for the largest share of financial and economic costs. Including vaccine program activity costs (US$ 4.68/per dose), the total financial cost was US$ 2, 911, 343 (US$ 7.75 per dose). Conclusion: This cost evaluation can support Senegal's future vaccine introductions and inform other countries planning to introduce HPV vaccine nationwide. These findings support previous costing studies which anticipated potential economies of scale during the transition from HPV vaccine pilot demonstration projects to national introduction.